Growth form classification for sessile suspension feeders and their distribution in Antarctic fjord, King George Island - Thorne, Daniela C.S.; Moreno, Bernabé; Indacochea, Aldo G. (Polish Polar Research, 2022)
Sessile suspension feeders depend primarily on availability of a space to settle and access to the water column. Their sessile nature incapacitates displacement during disturbances thus they rely on their morphology to overcome selective processes. We classified the assemblage of SSF from Mackellar Inlet (King George Island, Antarctica) according to their growth forms (GF) and epibiotic association type, the latter based on direct observation of the epibiotic behaviour of every individual. Organisms that did not comply with any previously established GF were grouped into ‘other GF’. Sampling stations were distributed across the fjord following a gradient based primarily on the distance to Domeyko Glacier (inner, middle, outer sections). Seven GF were recognised in the glaciomarine fjord: tree, bush, stalk, mound, flat, runner, and sheet. Four types of epibiotic associations were identified: basibiont, both facultative epibiont and basibiont, facultative epibiont (non-basibiont), and epibiont. Our results showed that the tree GF were found in the inner and middle sections, mound in middle and outer, and flat across all fjord sections. These GF enhanced GF-diversity since they constituted additional substrate for most of the ‘other GF’ which had primarily an epibiotic strategy. Contrastingly, bush, runner and stalk GF were only found in the outer section of the fjord, thus the most distanced from periglacial disturbances. The GF distribution was consistent with distance to glacier, both in number and strategies. These results highlight the potentialities of the morpho-functional classification applied to Antarctic sessile suspension feeders to help understand their distribution based on adaptive capabilities.